Highly effective sequencing whole chloroplast genomes of angiosperms by nine novel universal primer pairs. (7th April 2014) - Yang, Jun‐Bo; Li, De‐Zhu; Li, Hong‐Tao
Abstract Chloroplast genomes supply indispensable information that helps improve the phylogenetic resolution and even as organelle‐scale barcodes. Next‐generation sequencing technologies have helped promote sequencing of complete chloroplast genomes, but compared with the number of angiosperms, relatively few chloroplast genomes have been sequenced. There are two major reasons for the paucity of completely sequenced chloroplast genomes: (i) massive amounts of fresh leaves are needed for chloroplast sequencing and (ii) there are considerable gaps in the sequenced chloroplast genomes of many plants because of the difficulty of isolating high‐quality chloroplast DNA, preventing complete chloroplast genomes from being assembled. To overcome these obstacles, all known angiosperm chloroplast genomes available to date were analysed, and then we designed nine universal primer pairs corresponding to the highly conserved regions. Using these primers, angiosperm whole chloroplast genomes can be amplified using long‐range PCR and sequenced using next‐generation sequencing methods. The primers showed high universality, which was tested using 24 species representing major clades of angiosperms. To validate the functionality of the primers, eight species representing major groups of angiosperms, that is, early‐diverging angiosperms, magnoliids, monocots, Saxifragales, fabids, malvids and asterids, were sequenced and assembled their complete chloroplast genomes. In our trials, only 100 mg of fresh leaves was used. The results show that the universal primer set provided an easy, effective and feasible approach for sequencing whole chloroplast genomes in angiosperms. The designed universal primer pairs provide a possibility to accelerate genome‐scale data acquisition and will therefore magnify the phylogenetic resolution and species identification in angiosperms.